Effects of working capital management on profitability of media industry in South Korea and the comparison with Malaysia / Nabilah Abd Ghani - Abd Ghani, Nabilah (Faculty of Business Management, 2017)
As for South Korea, nobody in the world had imagined that their economy would grow so quickly after being destroyed by the Korean War (1950-1953). Even though at that time South Korea has no natural resources or infrastructure, but still their economics is rapidly growth and one of the reasons is due to their entertainment. According to (Hyejung, 2007) the South Korea wave reached an active penetration stage. This shows that their entertainment becomes globalized. The objectives are to identify the effect of working capital management on the profitability of media industry in South Korea and Malaysia and also to identify the comparison between the company’s profitability of the media industry in South Korea and Malaysia. By using Panel Data, multiple regression analysis is used where more than one independent variable to explain variance in the dependent variable. Not only that, T-test will be used to compare the profitability of the companies of Media Industry in South Korea and Malaysia. There are six total companies include three companies in South Korea and three companies in Malaysia. In this research, the independent variables include account receivable turnover, account payable turnover and current ratio, whereas the dependent variable is return on asset. As a result, both countries used Fixed Effect Model. However, for comparing the profitability, it shows in t-test that the profitability in Malaysia is better than South Korea.